Evaluation of the Prognostic Value of Red Cell Distribution Width to Total Serum Calcium Ratio in Patients with Acute Pancreatitis - Tian-Yong Han; Tao Cheng; Bo-Fu Liu; Ya-Rong He; Pan Pan; Wen-Tao Yang; Qiang-Lai; Yu Cao (Gastroenterology Research and Practice)
Introduction. Acute pancreatitis (AP) is a sudden inflammatory process in the pancreas with variable involvement of nearby organs or other organ systems, and it is a common cause for hospitalization of gastrointestinal origin. Early prediction of the prognosis of patients with AP is important to help physicians triage the patients and decrease mortality. Red cell distribution width (RDW) and total serum calcium (TSC) have been reported to be useful predictors of the severity of AP, but if these parameters are associated with the prognosis of AP is unknown. The objective of the study was to evaluate whether RDW/TSC can be used to predict the prognosis of patients with AP at an early stage. Methods. We retrospectively enrolled AP patients admitted to the emergency department of West China Hospital of Sichuan University from January 1, 2016, to June 30, 2016. According to the prognosis, AP patients were divided into ICU group and non-ICU group, surgery group and nonsurgery group, and hospital survival group and hospital death group. Demographic information and clinical and laboratory parameters of all enrolled patients after being admitted to ED were compared between the groups. The receiver operator characteristic (ROC) curves were used to evaluate the prognostic values of RDW, TSC, and RDW/TSC in patients with AP. Results. A total of 666 AP patients were enrolled in this study, with an average age of 47.99±14.11 years, including 633 patients who survived to discharge and 33 patients who died during hospitalization. The areas under the curve (AUC) of RDW and RDW/TSC predict that patients need to be admitted to ICU (0.773 vs. 0.824 vs. 0.723), patients need surgery treatment (0.744 vs. 0.768 vs. 0.690), and patients survived to hospital discharge (0.809 vs. 0.855 vs. 0.780) were greater than that of TSC, with RDW/TSC being the greatest. Conclusions. RDW/TSC may be a new method to identify the AP patients who need to be transferred to the ICU, accompanying complications which need surgery treatment, or may be died in hospital at an early stage, and we should pay more attention to RDW/TSC in patients with AP, for they may have a worse prognosis.